Single-Center Experience of Focal Thermo-Ablative Therapy After Pelvic Radiotherapy for In-Field Prostate Cancer Oligo-Recurrence - Giraud, Nicolas; Buy, Xavier; Vuong, Nam-Son; Gaston, Richard; Cazeau, Anne-Laure; Catena, Vittorio; Palussiere, Jean; Roubaud, Guilhem; Sargos, Paul (Frontiers in Oncology, 2021)
Purpose In-field prostate cancer (PCa) oligo-recurrence after pelvic radiotherapy is a challenging situation for which metastasis-directed treatments may be beneficial, but options for focal therapies are scarce. Methods We retrospectively reviewed data for patients with three or less in-field oligo-recurrent nodal, bone and/or locally recurrent (prostate, seminal vesicles, or prostatic bed) PCa lesions after radiation therapy, identified with molecular imaging (PET and/or MRI) and treated by focal ablative therapy (cryotherapy or radiofrequency) at the Institut Bergonié between 2012 and 2020. Chosen endpoints were the post-procedure PSA response (partially defined as a >50% reduction, complete as a PSA <0.05 ng/ml), progression-free survival (PFS) defined as either a biochemical relapse (defined as a rise >25% of the Nadir and above 2 ng/ml), radiological relapse (on any imaging technique), decision of treatment modification (hormonotherapy initiation or line change) or death, and tolerance. Results Forty-three patients were included. Diagnostic imaging was mostly 18F-Choline positron emission tomography/computerized tomography (PET/CT) (75.0%), prostate specific membrane antigen (PSMA) PET/CT (9.1%) or a combination of pelvic magnetic resonance imaging (MRI), CT, and 99 mTc-bone scintigraphy (11.4%). PSA response was observed in 41.9% patients (partial in 30.3%, complete in 11.6%). In the hormone-sensitive exclusive focal ablation group (n = 31), partial and complete PSA responses were 32.3 and 12.9% respectively. Early local control (absence of visible residual active target) on the post-procedure imaging was achieved with 87.5% success. After a median follow-up of 30 months (IQR 13.3–56.8), the median PFS was 9 months overall (95% CI, 6–17), and 17 months (95% CI, 11–NA) for PSA responders. Complications occurred in 11.4% patients, with only one grade IIIb Dindo–Clavien event (uretral stenosis requiring endoscopic uretrotomy). Conclusion In PCa patients showing in-field oligo-recurrence after pelvic radiotherapy, focal ablative treatment is a feasible option, possibly delaying a systemic treatment initiation or modification. These invasive strategies should preferably be performed in expert centers and discussed along other available focal strategies in multi-disciplinary meetings.